Contribution of astrocytes and macrophage migration inhibitory factor to immune-mediated canine encephalitis caused by the distemper virus - De Nardo, Tatianna F.S. [UNESP]; Bertolo, Paulo H.L. [UNESP]; Bernardes, Priscila A. [UNESP]; Munari, Danísio P. [UNESP]; Machado, Gisele F. [UNESP]; Jardim, Luciana S.; Moreira, Pamela R.R. [UNESP]; Rosolem, Mayara C. [UNESP]; Vasconcelos, Rosemeri O. [UNESP] (Elsevier, 2020)
Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine that is produced by many cell types in situations of homeostasis or disease. One of its functions is to act as a proinflammatory molecule. In humans, several studies have shown that MIF levels become elevated in the serum, urine, cerebrospinal fluid and tissues of patients with chronic inflammatory diseases (systemic lupus erythematosus, rheumatoid arthritis, multiple sclerosis, sepsis, atheromas, diabetes and cancer). In dogs, distemper is a viral infectious condition that may lead to demyelination and inflammation in the central nervous system (CNS). In addition to the action of the virus, the inflammatory process may give rise to lesions in the white matter. Therefore, the objectives of the present study were to evaluate the role of MIF in the encephalitis that the canine distemper virus causes and to compare this with immunodetection of major histocompatibility complex-II (MHC-II), CD3 T lymphocytes, MMP-9 and glial fibrillary acidic protein (GFAP; astrocytes) in demyelinated areas of the encephalon, in order to ascertain whether these findings might be related to the severity of the encephalic lesions. To this end, a retrospective study on archived paraffinized blocks was conducted, in which 21 encephala from dogs that had been naturally infected with the canine distemper virus (infected group) and five from dogs that had been free from systemic or CNS-affecting diseases (control group) were used. In the immunohistochemical analysis on the samples, the degree of marking by GFAP, MHC-II, MMP-9 and MIF was greater in the demyelinated areas and in the adjacent neuropil, and this was seen particularly in astrocytes. Detection of CD3 was limited to perivascular cuffs. In areas of liquefactive necrosis, Gitter cells were positive for MMP-9, MIF and MHC-II. Hence, it was concluded that activated astrocytes influenced the afflux of T lymphocytes to the encephalon (encephalitis). In the more advanced phases, activated phagocytes in the areas of liquefactive necrosis (Gitter cells) continued to produce inflammatory mediators even after the astrocytes in these localities had died, thereby worsening the encephalic lesions. Distemper virus-activated astrocytes and microglia produce MIF that results in proinflammatory stimulus on glial cells and brain-infiltrating leukocytes. Therefore, the effect of the inflammatory response is potentiated on the neuropil, resulting in neurological clinical signs.
Keywords: Demyelination; Dog; Immune response; Neuroinflammation; Virus